Экспериментальные исследования электротермической стойкости металлических элементов летательного аппарата к прямому воздействию тока искусственной молнии. Часть 1: Стойкость алюминиевой обшивки - Баранов, М.И.; Кравченко, В.И.; Носенко, М.А. (Електротехніка і електромеханіка, 2011)
Experimental a way are the results of melting got and according to electro-thermal stability executed from different aluminium alloys with the different thicknesses of sheet standards of edging of aircraft in the case of direct separate or joint action on them impulsive A- or protracted C- components of current of artificial lightning with the rationed peak-temporal parameters.